The (mis)education of African descendants in Portugal: towards vocational traps? - Abrantes, P.; Roldão, C. (Portuguese Journal of Social Science, 2019)
The expansion of vocational tracks is among the recent transformations of the Portuguese educational system. This policy measure entails risks of increasing ethno-racial segregation and institutional racism, especially considering the lack of monitoring programmes and the historically high-grade retention rates of the educational system. The experience of African immigrants and their offspring in Portugal is marked by a long history of racism associated with colonialism. Drawing on official data from multiple sources for the period between 2008–09 and 2013–14, this article examines developments in ethno-racial segregation in the educational system. Massive grade retention rates and a major orientation towards vocational tracks are apparent among students of African descent. Differences in comparison with their peers of Portuguese origin are striking, even considering students from similar class backgrounds.